Konsekuensi Logis Pencabutan Pasal 11 Ayat (1) Dan Ayat (2) Undang-Undang Nomor 36 Tahun 2014 Tentang Tenaga Kesehatan (Studi Kasus Putusan Mahkamah Konstitusi Nomor 82/Puu-Xiii/2015) - Karel Batmanlusi (Jurnal Ners, 2026)
ABSTRACT The Constitutional Court Decision Number 82/PUU-XIII/2015 declared Article 11 paragraphs (1) and (2) of Law Number 36 of 2014 on Health Workers unconstitutional and legally non-binding. This decision has significant juridical implications for the regulation of health workers, particularly regarding the distribution of authority between the state and professional organizations. This study aims to analyze the logical consequences of the annulment of these provisions, its juridical implications for the position and authority of professional organizations, and its impact on the post-decision health workforce regulatory system. This research employs a normative legal method using statutory and case approaches by examining Constitutional Court decisions, relevant legislation, and legal doctrines. The findings indicate that the annulment of Article 11 paragraphs (1) and (2) reaffirms the state’s primary authority and responsibility in regulating health workers to ensure legal certainty, service quality, and the protection of constitutional rights. The decision also repositions professional organizations as partners of the state in fostering professional development, rather than as holders of decisive public authority. Keywords: Constitutional Court, Health Workers, Rule of Law, Professional Organizations, State Authority.